On the challenges of establishing disjoint QoS IP/MPLS paths across multiple domains - Yannuzzi, Marcelo; Masip-Bruin, Xavi; Sanchez, Sergio; Domingo-Pascual, Jordi; Orda, Ariel; Sprintson, Alex (IEEE communications magazine, 2006)
MPLS is being actively adopted as the core switching infrastructure at the intradomain level. This trend is mainly attributable to the undeniable potential of MPLS in terms of virtual private networks (VPNs) management, traffic engineering (TE), QoS delivery, path protection, and fast recovery from network failures. However, little progress has been made to attain the expected extension of MPLS label-switched paths (LSPs) across domain boundaries. Among the problems that remain unsolved is how to efficiently find and establish primary and protection interdomain LSPs for mission-critical services subject to QoS constraints. This article explores the major limitations hindering the deployment of these kinds of LSPs across multiple domains, in the context of the current interdomain network model. We describe the critical problems faced by the research community, and present our vision on how to rationally overcome some of the problems exposed. Our perspective is that we should be prepared for rather coarse-grained solutions as long as we need to coexist with the current interdomain network model